NEK7 Coordinates Rapid Neuroinflammation After Subarachnoid Hemorrhage in Mice - Li, Gen; Dong, Yushu; Liu, Dongdong; Zou, Zheng; Hao, Guangzhi; Gao, Xu; Pan, Pengyu; Liang, Guobiao (Frontiers in Neurology, 2020)
Background: Subarachnoid hemorrhage (SAH) is a devastating disease lead to high morbidity and mortality. Recent studies indicated never in mitosis gene A-related expressed kinase 7 (NEK7) involved in NLRP3 (NLR family, pyrin domain containing 3) associated inflammation which may result in subsequent cellular and vascular damage. Aim of this study was to investigate whether NEK7 is involved in pathophysiology of subarachnoid hemorrhage. Methods: 455 adults male C57B6J mice, weighing 22 to 30g, were used to investigate the time course of NEK7 expression in ipsilateral cortex after SAH, the intrinsic function and mechanism of NEK7. Vascular puncture model was used to made mice SAH model, intracerebroventricular injection was used to delivery NEK7 recombinant protein, NE7 small interfering RNA, nigericin and MCC950. Neurological score, brain water content, Evans blue extravasation, immunoﬂuorescence and western blot were evaluated for neurological outcome, neuronal apoptosis, blood-brain barrier damage, microglia accumulation and mechanism of NEK7 and NLRP3 activation. Results: Our results exhibited that intrinsic NEK7 elevated after SAH in cortex of left/ipsilateral hemisphere and was colocalized with microglia, endothelial cells, neuron, astrocyte, and oligodendrocyte, and highly expressed in microglia and endothelial cells after SAH. NEK7 recombinant protein aggravated neurological deficits, brain edema, neuronal apoptosis, BBB permeability, microglial accumulation and activated caspase-1 and IL-1β maturation, NE7 small interfering RNA injection reversed those effect. Nigericin administration enhancing ASC oligomerization, caspase-1 and IL-1β maturation without increasing protein level of NLRP3, and ASC oligomerization and caspase-1 IL-1β maturation reduced when combined with NEK7 knockdown or MCC950 delivery. We found level of NEK7 expression increased after SAH and could activate downstream NLRP3 pathway to induce caspase-1, IL-1β expression and then increasing BBB opening microglia accumulation and neuronal apoptosis after SAH. Conclusions: This study demonstrated for the first time that NEK7 mediated the harmful effects of on neuronal apoptosis and BBB disruption after SAH, which potentially mediated by NEK7/NLRP3 signal. NEK7 served as co-component for NLRP3 inflammasome activation after SAH. NEK7 may be a promising target on the management of SAH patients.